Synthesis and characterization of transferrin-targeted chemotherapeutic delivery systems prepared via RAFT copolymerization of high molecular weight PEG macromonomers - Roy, Debashish (2013)
Reversible addition-fragmentation chain transfer (RAFT) polymerization was employed to prepare a nanoparticulate drug delivery system for chemotherapeutics. The nanoparticles contain a PEG “stealth” corona as well as reactive anhydride functionality designed for conjugating targeting proteins. The multifunctional carrier functionality was achieved by controlling the copolymerization of the hydrophobic monomer lauryl methacrylate (LMA), with a reactive anhydride functional methacrylate (TMA), and a large polyethyleneglycol methacrylate monomer (M(n)~950 Da) (O950). RAFT polymerization kinetics of O950 were evaluated as a function of target degrees of polymerization (DP), initial chain transfer agent to initiator ratio ([CTA](o)/[I](o)), and solvent concentration. Excellent control over the polymerization was observed for target DPs of 25 and 50 at [CTA](o)/[I](o) ratio of 10 as evidenced by narrow and symmetric molecular weight distributions and the ability to prepare block copolymers. The TMA-functional copolymers were conjugated to the tumor targeting protein transferrin (Tf). The targeted copolymer was shown to encapsulate docetaxel at concentrations comparable to the commercial single vial formulation of docetaxel (Taxotere). In vitro cytotoxicity studies conducted in HeLa cells show that the Tf targeting enhances the cancer killing properties relative to the polymer encapsulated docetaxel formulation.